EDUCATION FOR INFORMATION SCIENCE: AN APOLOGIA AND AN INTRODUCTION / (L’EDUCATION POUR LES SCIENCES DE L’INFORMATION APOLOGIA ET UNE INTRODUCTION) - Batty, C. David (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2022)
see pdf